ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTA PROVINSI JAWA TENGAH - Rizqi Dwi Setianingrum; Haryanto Haryanto (Diponegoro Journal of Accounting, 2020)
The study aims to analysis of financial performance of regency and city governments in Central Java Province, is providing an important information in find out how the level of success implementing regional autonomy and transparent local financial management to run the welfare of society. One of the lays to analyze the government’s financial is to run an analysis the financial ratio. The purpose of this study is to find out the financial performance capabilities of local government of regency and city in Central Java Province from 2016 until 2018. The research method used is quantitave descriptive to measure the financial performance with ratio, the data used is in the form of Budget Realization Report and Balance. The results of the research reveals that: Sukoharjo Regency and Semarang City is highest of decentralized ratio, and Blora Regency and Pekalongan City is lowest of decentralized ratio. Cilacap Regency and Semarang City is highest of independence ratio and Blora Regency and Pekalongan City is lowest of independence ratio. The effectiveness ratio, Sukoharjo Regency and Salatiga City is highest and Magelang Regency and Pekalongan City is lowest. The harmony ratio: operating expense ratio, Batang Regency and Tegal City is highest and Demak Regency and Semarang City is lowest, capital expenditure ratio, Demak Regency and Semarang City is highest and Batang Regency and Tegal City is lowest. The growth ratio, Klaten Regency and Magelang City is highest and Temanggung Regency and Tegal City is lowest. The liquidity ratio: current ratio, Wonosobo Regency and Magelang City is highest and Temanggung Regency and Surakarta City is lowest.